ANALISIS CAPAIAN BELAJAR SISWA SMAN DI INDONESIA TAHUN 2019 DENGAN PEMODELAN MIXED GEOGRAPHICALLY WEIGHTED REGRESSION - Febrianto Nainggolan; Ernawati Pasaribu (Politeknik Statistika STIS, 2020)
National student learning outcomes so far have been measured by the results of the National Examination (NE). The distribution of NE scores for high school students in Indonesia tends to be uneven, with high learning outcomes only on the island of Java. Ironically, regions in Eastern Indonesia have a very low average NE score. The interesting thing is that regions with the same value categories tend to be close together and indicate a regional effect on learning outcomes in Indonesia. This study analyzes the characteristics and factors that influence the learning achievement of district/city high school students in Indonesia in 2019 using the mixed Geographically Weighted Analysis (mixed GWR) model approach. The results found that there were effects of spatial autocorrelation and spatial heterogeneity in the modeling of district / city level high school NE scores and the factors that influenced them in Indonesia in 2019. Analysis using the mixed GWR method produced variable conditions of classroom buildings, ratio of students per class, and Teacher competency Test scores influences learning outcomes locally in each district/city. Meanwhile, per capita GRDP has a global effect on learning outcomes. Suggestions are given to improve classroom buildings, a more equitable distribution of students per class and the distribution of high-ability teachers. In addition, it is necessary to hold a test form that can better describe the quality of education in Indonesia, in lieu of the National Examination.